2021
DOI: 10.1016/j.clon.2021.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Overview of the Preclinical and Clinical Radiobiology of Microbeam Radiotherapy

Abstract: Microbeam radiotherapy (MRT) is the delivery of spatially fractionated beams that have the potential to offer significant improvements in the therapeutic ratio due to the delivery of micron-sized high dose and dose rate beams. They build on longstanding clinical experience of GRID radiotherapy and more recently lattice-based approaches. Here we briefly overview the preclinical evidence for MRT efficacy and highlight the challenges for bringing this to clinical utility. The biological mechanisms underpinning MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Spatially fractionated radiation therapy was first used to exploit the advantage of skin-sparing effects in patients while enabling a high dose rate to refractory tumours in palliative treatments. Potential use of GRID, or other applications of SFRT, such as MRT, beyond the original palliative applications, and even multi-technique approaches [ 7 , 8 ] have been investigated due to findings of a greater therapeutic index resulting from both the increased normal tissue sparing and the greater tumour toxicity when compared to conventional temporally fractionated radiation therapy [ 9 , 10 , 11 , 12 ].…”
Section: Molecular and Radiobiological Mechanisms Of Spatially Fracti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Spatially fractionated radiation therapy was first used to exploit the advantage of skin-sparing effects in patients while enabling a high dose rate to refractory tumours in palliative treatments. Potential use of GRID, or other applications of SFRT, such as MRT, beyond the original palliative applications, and even multi-technique approaches [ 7 , 8 ] have been investigated due to findings of a greater therapeutic index resulting from both the increased normal tissue sparing and the greater tumour toxicity when compared to conventional temporally fractionated radiation therapy [ 9 , 10 , 11 , 12 ].…”
Section: Molecular and Radiobiological Mechanisms Of Spatially Fracti...mentioning
confidence: 99%
“…Growth in tumour blood supply is driven by strong angiogenic signalling to meet the high metabolic demands of tumour tissue. The resulting vasculature differs, however, from normal tissue vessels, being aberrant in both structure and function [ 9 , 15 ]. Tumour endothelium is of an immature phenotype that supports quick regeneration, but also mediates therapeutic resistance by actively blocking immune responses to cancer cells following radiation therapy [ 15 , 16 ].…”
Section: Molecular and Radiobiological Mechanisms Of Spatially Fracti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, dose-volume histogram analysis is commonly used as a countermeasure for adverse events associated with radiotherapy. However, as mentioned above, one defining characteristic of non-uniform exposures is that the observed dose-response relationships cannot be predicted from uniform exposures and then based on the standard radiobiological DNA damage and repair model [70]. Although advances in radiotherapy technology have recently made it possible to efficiently focus radiation doses on the planned target volume (PTV), a technology to completely irradiate only cancerous tissues has not yet been developed.…”
Section: Fertility Preservation In Patients After Radiotherapymentioning
confidence: 99%
“…The key physical parameters defining these beams for MRT are the beam cross-sections, the inter-beam distance, the peak to valley dose ratio, and the valley doses delivered due to scattering [70]. It has been reported that MRT exposure leads to a tissue-sparing effect (TSE) which is observable in various organs and species [85][86][87][88][89][90][91].…”
Section: Microbeam Radiotherapy As a Possible Approach For Oncofertilitymentioning
confidence: 99%